Dakwah Bagi Generasi Milenial Melalui Media Sosial - Zainal Azman (STAI Bumi Silampari, 2021)
The development of technology gave birth to an interesting phenomenon in people's lives today, namely the rise of global culture and an instant lifestyle. Technological developments have resulted in the da'wah model growing rapidly and dynamically and can affect the morals and morals of the millennial generation, where they are in the process of finding their identity. With the development of technology, it is undeniable that content that smells of radicalism, extremism can quickly spread and is able to enter all lines. So, we need a place that can bring fresh air so that the millennial generation does not easily trust content that is spread liberally. Da'wah for the millennial generation is da'wah whose implementation adapts the material, methods, and media of da'wah to the conditions of the millennial community (as the object of da'wah) which may not be the situation and conditions that occurred in the millennial era in the previous era, especially in the classical era.